IBM Power systems high availability and disaster recovery updates : planning for a multicloud environment - Quintero, Dino; Baumann, Thomas; Cruz, Vera; Haldar, Nilabja; Largou, Youssef; Pandey, Prashant; Pereira, Edson Gomes; Riesco, Diego; Roach, Douglas; Steel, Antony (IBM Redbooks, 2022)
This IBM℗ʼ Redpaper publication delivers an updated guide for high availability and disaster recovery (HADR) planning in a multicloud environment for IBM Power. This publication describes the ideas from studies that were performed in a virtual collaborative team of IBM Business Partners, technical focal points, and product managers who used hands-on experience to implement case studies to show HADR management aspects to develop this technical update guide for a hybrid multicloud environment. The goal of this book is to deliver a HADR guide for backup and data management on-premises and in a multicloud environment. This document updates HADR on-premises and in the cloud with IBM PowerHA℗ʼ SystemMirror℗ʼ, IBM VM Recovery Manager (VMRM), and other solutions that are available on IBM Power for IBM AIX℗ʼ, IBM i, and Linux. This publication highlights the available offerings at the time of writing for each operating system (OS) that is supported in IBM Power, including best practices. This book addresses topics for IT architects, IT specialists, sellers, and anyone looking to implement and manage HADR on-premises and in the cloud. Moreover, this publication provides documentation to transfer how-to skills to the technical teams and solution guidance to the sales team. This book complements the documentation that is available at IBM Documentation and aligns with the educational materials that are provided by IBM Systems Technical Training.